Peran Kepuasan dalam Memediasi Pengaruh Persepsi Nilai Pasca Pembelian Terhadap Minat Beli Ulang Pengguna Vending Machine Blue Mart: (The Role of Satisfaction in Mediating the Effect of Post Purchase Value Perceptions on Purchase Intention of Blue Mart Vending Machine Users) - Bayu Umara; Dudy Suryadi; Septi Isnaeni; Gita Yulianti; Yulia Tumini (LPPM Universitas Pelita Bangsa, 2021)
Every company strives to be able to attract consumers, starting with growing interest in buying. There are various ways to do it, one of which is done by Blue Mart, namely by providing a vending machine. Consumers are expected to have a good perception of value based on the experience or information of other parties who have made purchases through vending maching. This study aims to analyze the effect of perceived value on repurchase interest directly and indirectly through consumer satisfaction. The research was conducted by distributing questionnaires via google form during November 2020 to Vending Machine Blue Mart consumers. The questionnaires that were collected and met the criteria as research data were 186. Structural Equation Modeling using AMOS Version 23 was used to analyze the data. The research findings show that the perception of post-purchase value affects consumer repurchase interest in Blue Mart using vending machines directly or indirectly mediated by consumer satisfaction.